High Performance Self-Compacting Concrete with Electric Arc Furnace Slag Aggregate and Cupola Slag Powder - Israel Sosa (Applied Sciences, 2020)
The development of self-compacting concretes with electric arc furnace slags is a novelty in the field of materials and the production of high-performance concretes with these characteristics is a further achievement. To obtain these high-strength, low-permeability concretes, steel slag aggregates and cupola slag powder are used. To prove the effectiveness of these concretes, they are compared with control concretes that use diabase aggregates, fly ash, and limestone supplementary cementitious materials (SCMs, also called fillers) and intermediate mix proportions. The high density SCMs give the fresh concrete self-compacting thixotropy using high-density aggregates with no segregation. Moreover, the temporal evolution of the mechanical properties of mortars and concretes shows pozzolanic reactions for the cupola slag. The fulfillment of the demands in terms of stability, flowability, and mechanical properties required for this type of concrete, and the savings of natural resources derived from the valorization of waste, make these sustainable concretes a viable option for countless applications in civil engineering.